Caffeic Acid Induces Apoptosis in MG-63 Osteosarcoma Cells via Protein Kinase C Delta (PKCδ) Translocation and Mitochondrial Membrane Potential Reduction - Ferry Sandra; Muhammad Ihsan Rizal; Caecilia Caroline Aliwarga; Jenifer Christy Hadimartana; Maria Celinna (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Caffeic acid has been reported to activate caspases in MG-63 osteosarcoma cells, which can lead to apoptosis via both extrinsic and intrinsic apoptotic pathways. Translocation of protein kinase C delta (PKCδ), which reduces mitochondrial membrane potential (ΔΨm), is involved in apoptosis. The role of PKCδ translocation and ΔΨm alteration in caffeic acid-induced MG-63 cell apoptosis are largely unknown. Present study investigated the effect of caffeic acid on PKCδ translocation and ΔΨm in MG-63 cells.METHODS: MG-63 cells were cultured and starved, followed by pretreatment with or without Z-VAD-FMK and treatment with or without 10 μg/mL caffeic acid. MG-63 cells were collected, lysed, and processed to obtain cytosolic and mitochondrial fractions. Each fraction was subjected to immunoblotting analysis by using anti-PKCδ antibody. Mitochondrial membrane potential (ΔΨm) was measured using flow cytometry.RESULTS: Cytosolic PKCδ levels were higher than mitochondrial PKCδ levels in untreated and 1 h caffeic acid treatment groups. Inversely, cytosolic PKCδ levels were lower than the mitochondrial PKCδ levels after 6 and 12 h caffeic acid treatment. By Z-VAD-FMK pretreatment, cytosolic PKCδ levels were higher than mitochondrial PKCδ after 6 and 12 h caffeic acid treatment. After 6 h treatment with caffeic acid, ΔΨm was slightly shifted. More shifting occurred in MG-63 cells treated with caffeic acid for 12 h. The ΔΨm shifting was inhibited by Z-VAD-FMK pretreatment.CONCLUSION: Caffeic acid could trigger apoptosis of MG-63 osteosarcoma cells by inducing PKCδ translocation to mitochondria and reducing ΔΨm, which might cause MMP.KEYWORDS: caffeic acid, MG-63, osteosarcoma, PKCδ, mitochondrial membrane potential, mitochondrial membrane permeabilization, Z-VAD-FMK